Treating Chronic Tendinopathy: Physical Therapy, Surgery and Other Form of Therapy - Artur Łukawski; Julia Szałajska; Klaudia Wojtach; Filip Czyżewski; Iga Wiak; Filip Banyś; Konrad Bochen; Filip Jasiński; Anna Dziegciarczyk; Weronika Górska (Quality in Sport)
Introduction: The term "tendinopathy" refers to pathological changes in tendons. The previously used term "tendonitis" does not fully capture the nature of the condition, as inflammatory changes, when present, are secondary to degenerative damage. Tendinopathies are quite common in the general population.